A new cytotoxic compound from the leaves of Styrax annamensis Guillaumin. Issue 6 (19th March 2022) - Tra, Nguyen Thanh; Son, Ninh The; Van Tuyen, Nguyen; Cuong, Pham Van; Thu Ha, Nguyen Thi; Anh, Le Thi Tu; Huong, Doan Thi Mai; Ngan, Truong Bich; Litaudon, Marc
Abstract: New propene derivative 1-(3 ', 4 ' -methylenedioxyphenyl)-2-(2 '' -hydroxy-5-(3 ''' -hydroxypropyl)-3 '' -methoxyphenyl)prop-2-en-1-one (1 ), along with three known triterpenoids ursolic acid (2 ), pomolic acid (3 ), and maslinic acid (4 ) were isolated from the leaves of Styrax annamensis species. All structures were assigned by spectroscopic analysis. Compound 1 showed potent cytotoxicity against four cancer cell lines (KB, HepG2, Lu, and MCF7) with the IC50 values of 3.19, 2.87, 2.33, and 2.44 µM, respectively. GRAPHICAL ABSTRACT: